Implementation of the GATT State Rates Policy on International Trade - Marbun, Sonia Hapsari; Febrianti, Dwi; Matondang, Khairani (Journal of Business Management and Economic Development, 2023)
Tariff policy can be interpreted as a systematic arrangement of duties levied on goods and services that cross national borders. The purpose of this research is to find out how the implementation of tariffs or international agreements related to international trade, especially the General Tariffs and Trade (GATT) agreement. This research uses quantitative research methods through a descriptive research approach. The results of this study are GATT countries usually use a lot of tariff policies to protect domestic production and also to attract revenue to the country. Even though it is permissible, the use of these tariffs is still subject to GATT provisions and many rules and agreements issued by GATT.